Case Report: Outcome and Adverse Events of Anti-PD-1 Antibody Plus Chidamide for Relapsed/Refractory Sézary Syndrome: Case Series and A Literature Review - Chen, Chao; Liu, Zhaorui; Liu, Jie; Zhang, Wei; Zhou, Daobin; Zhang, Yan (Frontiers in Oncology, 2022)
Sézary syndrome (SS) is an aggressive leukemic variant of cutaneous T-cell lymphoma with a poor prognosis and survival rate. Existing therapies for relapsed/refractory (R/R) SS have a low response rate with a short duration time. Herein, we presented three cases of R/R SS treated with anti-PD-1 antibody and chidamide. Case 1 and case 2 showed the potential efficacy of this combination therapy with a long duration time. Case 2 and case 3 both showed the patients developed acute and transient worsening of erythema and pruritus after anti-PD-1 antibody infusion, and this flare reaction was associated with transient decreased leukocytes and lymphocytes in peripheral blood. To the best of our knowledge, this is the first report of anti-PD-1 antibody combined with chidamide for treatment of R/R SS. This report suggests that the combination therapy may be a new and effective treatment, and that further clinical trials are needed to prove it and elucidate the mechanism of this combination therapy and its flare reaction.